Perturbation analysis of two-stage continuous transfer lines subject to operation-dependent failures - Fu, M.; Xiaolan Xie (Proceedings of the 37th IEEE Conference on Decision and Control (Cat. No.98CH36171), 1998)
This paper addresses the perturbation analysis of transfer lines composed of two machines separated by a buffer of finite capacity. A continuous flow model is considered, where machines are subject to operation-dependent failures, i.e. a machine cannot fail when it is idle. Times to repair and times to failure of the machines are random variables with general distribution. The purpose of this paper is to evaluate the gradient of the throughput rate with respect to the buffer capacity. Both infinitesimal perturbation analysis (IPA) estimators and smoothed perturbation analysis (SPA) estimators are derived. Simulation results show that IPA estimators do not work, contradicting the common belief that IPA always works for continuous flow models.